Proteomics identifies Bacillus cereus EntD as a pivotal protein for the production of numerous virulence factors - Omer, Hélène; Alpha-Bazin, Béatrice; Brunet, Jean-Luc; Armengaud, Jean; Duport, Catherine (Frontiers in Microbiology, 2015)
Bacillus cereus is a gram-positive pathogen that causes a wide variety of diseases in humans. It secretes into the extracellular milieu proteins that may contribute directly or indirectly to its virulence. EntD is a novel exoprotein identified by proteogenomics of B. cereus ATCC 14579. We constructed a ΔentD mutant and analyzed the impact of entD disruption on the cellular proteome and exoproteome isolated from early, late and stationary-phase cultures. We identified 308 and 79 proteins regulated by EntD in the cellular proteome and the exoproteome, respectively. The contribution of these proteins to important virulence-associated functions, including central metabolism, cell structure, antioxidative ability, cell motility and toxin production, are presented. The proteomic data were correlated with the growth defect, cell morphology change, reduced motility and reduced cytotoxicity of the ΔentD mutant strain. We conclude that EntD is an important player in B. cereus virulence. The function of EntD and the putative EntD-dependent regulatory network are discussed. To our knowledge, this study is the first characterization of an Ent family protein in a species of the B. cereus group.